Flapper Valve and Hayfork: Functional anatomy and taxonomic potential of the Gastric Mill of Bairdioidea (Ostracoda, Podocopida) - Maddocks, Rosalie F. (Zootaxa, 2018)
The chewing apparatus of the Bairdioidea has been described just once and is rarely illustrated, but it might have more taxonomic significance than commonly supposed. It is constructed as a flapper valve (hinged check valve), which is unique among Ostracoda and unusual among animals. It projects into the midgut and is substantially enveloped by it. It serves three functions: to move bites of food into the stomach, to close the esophagus against back-flow, and to pack strands of food and mucus onto the rotating food ball. It is probably less effective for macerating the food to reduce particle size. Two braces anchor this structure to the lateral wall of the forehead. It is lined by cuticle that is shed at each molt, and the formation of food balls is interrupted during molting. In its construction and action, this apparatus is quite unlike the gastric mill of decapod crustaceans, and it shows only distant homology to the dorsal Wulst of Cypridoidea. Some architectural details differ among families and genera. The well-sclerotized plate has some potential for fossil preservation in exceptional circumstances. A revised anatomical analysis is presented, together with an annotated glossary of terms.